Preparation, Characterization and Biological Studies of New Tetra-Dentate N4 Schiff Base Derived from Malonic Acid Dihydrazide with Mn+2 and Co+2 Complexes - Hammoda, Rehab Galib (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
New complexes were synthesized from a newly prepared Schiff base ligand (L2) derived from malonic acid dihydrizde and 2- pyridine carboxaldehyde. The 1H-NMR and 13C-NMR spectra demonstrated all the needed peaks to prove the chemical structure of the synthesized ligand (L2). Utilizing mass spectroscopy, the molecular ion peak was found at m/e 310, confirming the formula weight for L2, which matches the estimated m+ value (310.12). Accordingly, its Mn (II) and Co (II) complexes were trainedusing glacial acetic acid as a catalyst. These compounds were characterized by FT-IR, UV-Vis, C.H.N., chloride-containing, molar conductance, magnetic susceptibility, and atomic absorption. The characterization results gave complexes hexadentate coordination geometry for each cobalt and manganese complex. Schiff base ligand acted as tetradentate with a good yield. The biological activities of the new compounds were valued against two Gram-positive (Staphylococcus aureus and Bacillus subtitles), two Gram-negative (Escherichia coli and Pseudomonas aeruginosa), and candida fungi; hence, their results were good in inhibition